Spelling Bee Competition Trophy Rector of Bina Darma 2018 - Ferry Kurniawan; Sunda Ariana; Rosmaidar Rosmaidar (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2020)
Global competition has demanded every individual to have strong competitiveness on a national and international scale. Proficiency in language is also a demand in global competition. Language is also a medium that can influence someone and is a media used to express opinions and analyze problems. As a lecturer who takes shelter in the English study program, there is a desire to conduct guidance in the language field for lecturers and employees of Bina Darma University as one of the community service activities. Therefore Bujang Girls Campus Bina Darma University was chosen to conduct Spelling Bee Competition activities to provide motivation to learn English for lecturers and employees of Bina Darma University .. The mission of the Spelling Bee Comepetion activity is to provide additional knowledge of English which is expected to be able to increase English proficiency for Bina Darma University lecturers and employee. Keywords: Spelling, Bee, Competition